The Influence of Green Practices, Digital Service Transformation, and Internal Organizational Capability on Sustainable Performance: The Mediating Role of Business Model Innovation - Loogsorn, Thanusak; U-on, Vichit (Journal of Cultural Analysis and Social Change, 2026)
This study examines the causal relationships among green management, digital service transformation, internal capability, business model innovation (BMI), and sustainable performance within Thailand’s apartment rental industry. Rapid urbanization, intensifying market competition, and evolving customer expectations have increased the need for apartment operators to adopt sustainable and innovative business practices. Guided by system theory, this research employs a mixed-method explanatory approach to investigate how organizational inputs, environmental practices, digital readiness, and internal competencies, are transformed into sustainable outcomes through BMI. The qualitative phase, involving interviews with five industry experts, confirmed the contextual relevance and conceptual dimensions of all variables. The quantitative phase used survey data collected from 360 apartment operators nationwide, analyzed through Structural Equation Modeling (SEM) to validate the proposed model and test the direct and indirect effects among variables. Results indicate that all key variables, green management, digital service transformation, internal capability, BMI, and sustainable performance, were present at moderate levels, reflecting partial but growing adoption across the sector. SEM findings demonstrate that all seven hypotheses were supported, with internal capability exerting the strongest influence on BMI. Furthermore, BMI showed a significant direct effect on sustainable performance and served as a full or partial mediator in all causal pathways, confirming its central role in transforming organizational practices into sustainability outcomes. The study contributes to theoretical advancement by integrating digital, environmental, and capability-based perspectives into a unified model and offers practical insights for apartment operators seeking to enhance competitiveness through green practices, digital innovation, and capability development. Policy recommendations include promoting green incentives and digital transformation support for SMEs. Future research should examine longitudinal effects and extend the model to other rental accommodation sectors.